2018
DOI: 10.1186/s12884-018-1977-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a participatory community quality improvement strategy on improving household and provider health care behaviors and practices: a propensity score analysis

Abstract: BackgroundMaternal and newborn health care intervention coverage has increased in many low-income countries over the last decade, yet poor quality of care remains a challenge, limiting health gains. The World Health Organization envisions community engagement as a critical component of health care delivery systems to ensure quality services, responsive to community needs. Aligned with this, a Participatory Community Quality Improvement (PCQI) strategy was introduced in Ethiopia, in 14 of 91 rural woredas (dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…These findings are in line with a systematic review of participatory learning and action cycles with women's groups reporting improved clean home-delivery practices and uptake of any ANC [35], and with other studies on participatory community QI approaches that reported improved use of maternal health services [33,37].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…These findings are in line with a systematic review of participatory learning and action cycles with women's groups reporting improved clean home-delivery practices and uptake of any ANC [35], and with other studies on participatory community QI approaches that reported improved use of maternal health services [33,37].…”
Section: Discussionsupporting
confidence: 87%
“…Mixed findings were reported from women's group trials. It is in line with a previous quasi-experimental study in Ethiopia that engaged communities in identifying barriers to access and quality of services and reported an 11 percentage-point increase in average treatment effect in institutional deliveries [37]. But it is inconsistent with other studies elsewhere.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations